Influence of digitalization processes on the functioning of the banking - A. I. Vagabova (Путеводитель предпринимателя, 2020)
This article deals with modern directions of digital fiscal policy in Russian banking. It considers main problems which Russian banking system is facing now and analyses the influence fiscal policy has on banking